A silicone treatment compared to traditional natural fiber treatments: Effect on the mechanical and viscoelastic properties of jute-vinylester laminates - Stocchi, Ariel Leonardo (2007)
In this work vinylester-matrix composites reinforced with woven jute fabrics were investigated. The effect of a simple fiber treatment with silicone on the mechanical and viscoelastic response in comparison to traditional treatments was analyzed. Unless the composite with acetylated fibers, all composites exhibited higher values of rubbery storage modulus than the matrix. All treated fiber composites have similar damping capacities. Furthermore, silicone had a plasticizing effect on the vinylester matrix. The composites with washed fibers and with fibers treated with silicone exhibited slightly higher stiffness and strength values than other treated fiber composites. In addition to its experimental simplicity, the treatment with silicone also allowed us to obtain the composites with best combination of stiffness, strength, and toughness.